2021
DOI: 10.1021/jacs.1c05251
|View full text |Cite
|
Sign up to set email alerts
|

[n]Cyclodibenzopentalenes as Antiaromatic Curved Nanocarbons with High Strain and Strong Fullerene Binding

Abstract: Conjugated nanohoops provide a platform to study structure–property relationships; they are attractive hosts for supramolecular chemistry as well as promising candidates as new organic materials. We herein present [n]­cyclodibenzo­pentalenes ([n]­CDBPs) as antiaromatic analogues of [n]­cycloparaphenylenes. Platinum-mediated macrocyclization of dibenzopentalene boronic esters provided the trimer and tetramer with strain energies of up to 80 kcal mol–1. In the solid state, the cylindrical [4]­CDBP molecules alig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(87 citation statements)
references
References 58 publications
3
72
1
4
Order By: Relevance
“…In the structurally related indeno[1,2-b]fluorenes, transient absorption spectroscopy measurements showed that the excited-state lifetimes were shorter than the timescale at which fluorescence is usually observed. 84 We also did not observe fluorescence for those hoops, in which the -system is dominated by DBPs, namely [n]CDBPs 2 and 3, 16 [n]C-5,10-DBPs 4 and 5, 18 51 On the other hand, in [2]DBP [12]CPP 6 13 and DBP[n]CPPs 8 and 9, 17 which consist of DBPs alternating with [6]-or [7]paraphenylene linker(s), we were able to detect fluorescence, albeit of low intensity. This fluorescence stemmed from the paraphenylene units, which explains the similar wavelengths and shapes of the emission bands, with maxima at 471 nm (6), 487 nm (8), and 479 nm (9), corresponding to a bathochromic shift with increasing strain (the spectra of 8 and 9 are shown in Figure 8B).…”
Section: Electronic Propertiesmentioning
confidence: 72%
See 1 more Smart Citation
“…In the structurally related indeno[1,2-b]fluorenes, transient absorption spectroscopy measurements showed that the excited-state lifetimes were shorter than the timescale at which fluorescence is usually observed. 84 We also did not observe fluorescence for those hoops, in which the -system is dominated by DBPs, namely [n]CDBPs 2 and 3, 16 [n]C-5,10-DBPs 4 and 5, 18 51 On the other hand, in [2]DBP [12]CPP 6 13 and DBP[n]CPPs 8 and 9, 17 which consist of DBPs alternating with [6]-or [7]paraphenylene linker(s), we were able to detect fluorescence, albeit of low intensity. This fluorescence stemmed from the paraphenylene units, which explains the similar wavelengths and shapes of the emission bands, with maxima at 471 nm (6), 487 nm (8), and 479 nm (9), corresponding to a bathochromic shift with increasing strain (the spectra of 8 and 9 are shown in Figure 8B).…”
Section: Electronic Propertiesmentioning
confidence: 72%
“…12 Despite the tremendous diversity of nanohoops that have been reported in the past ten years, carbon nanohoops containing antiaromatic units had remained unexplored until recent reports from our group. [13][14][15][16][17][18] The electronic properties of antiaromatic molecules are markedly different from those of aromatic compounds, manifested in higher HOMO and lower LUMO energies and higher reactivities, among others. When we entered the field, little was known regarding how bending and cyclic conjugation would alter the properties of antiaromatic systems.…”
Section: Account Synlettmentioning
confidence: 99%
“…[125] Most recently, they synthesized fully conjugated macrocycles containing only DBPs within (e. g. [4]DBP 128 and [3]DBP 129) in which increasing strain caused an increase in aromaticity. [126] In 2014, Nakano et al polymerized DBPs derivatives (Figure 18). Regardless of the polymerization direction through the DBP core, the LUMOs tended to localize on the DBP units, with minor extents of delocalization onto the linear polymers.…”
Section: Pentalenementioning
confidence: 99%
“… Dibenzopentalene macrocycles, including cyclophanes, CPPs, and all dibenzopentalene rings. The macrocycles are arranged in increasing strain energy from top left to bottom right [124–126] …”
Section: Pentalenementioning
confidence: 99%
See 1 more Smart Citation